Selective Regulation of B-Raf Dependent K-Ras/Mitogen-Activated Protein by Natural Occurring Multi-kinase Inhibitors in Cancer Cells - Abd El Maksoud, Ahmed I.; Taher, Rehab F.; Gaara, Ahmed H.; Abdelrazik, Eman; Keshk, Omar S.; Elawdan, Khaled A.; Morsy, Salwa E.; Salah, Ahmed; Khalil, Hany (Frontiers in Oncology, 2019)
Introduction: Cancer is one of the most difficult challenges faced by humanity due to its many associated issues, such as inability to prevent diseases, treatment safety, and high mortality rate. In cancer, a variety of cellular signaling is activated to ensure malignancy transformation, angiogenesis and metastasis. The most efficient signaling pathway in cancer is mitogen-activated protein kinase (MAPK), which controls malignancy and regulates apoptosis. Methods: Four different flavonoid glycosides have been isolated from Pulicaria jaubertii using the phytochemical characterization of hydro-methanol extract. The purified glycosides (PJs) were investigated for their potential repression of cancer development using human lung epithelial cells and hepatocellular carcinoma (HCC) and compared with Sorafenib (SOR), the standard systemic drug for HCC. In PJ-treated cells, the expression profile of K-Ras, B-Raf, and P53 were detected using qRT-PCR, flow cytometry, confocal microscopy and western blot. Steady-state mRNA and levels of transforming growth factor-beta (TGF-β) and interleukin 8 (IL-8) were monitored in the fluids media at different time points following treatment. Results: Our results showed that the qurictine glycosides (PJ-1 and PJ-9) selectively inhibited the mutant K-Ras/B-Raf proteins expression and interaction in both cancer cells; while SOR showed obvious depletion of total Raf-1 protein in cancer cells and normal cells as well. Interestingly, the combination of PJ-1 or PJ-9 with SOR exhibited restoring cell viability of normal cells via controlling Raf-1 and P53 genes expression. Further, these identified PJ agents significantly adjusted the levels of TGF-β and IL-8 in cancer treated cells accompanied by restoring the activation of P53 expression. These findings were confirmed by docking analysis of PJs ligand and the crystal structure of K-Ras, B-Raf, and ERK transcription factor. Conclusion: The current data provide novel and natural multi-kinase inhibitors with competitive regulation of the mutant proteins; K-Ras and B-Raf and sustained MAPK signaling without any detectable toxic effect in normal cells.